2020
DOI: 10.1192/j.eurpsy.2020.102
|View full text |Cite
|
Sign up to set email alerts
|

Are we training psychiatrists to develop skills in intellectual disability psychiatry? Current European context and future directions

Abstract: The majority of people with intellectual disabilities (ID) and psychiatric disorders access mainstream mental health services across Europe. However, only 56% of countries provide postgraduate psychiatric training in ID according to a survey across 42 European countries. We explore the challenges of ID training and make recommendations for education and health policymakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Although the risk of mental disorders among Polish PwID is up to three times higher than in the general population, they lack adequate diagnostic tools and specialists (Rękosiewicz, 2018). No special category for ID Psychiatry exists in Polish psychiatric training, and no inpatient or outpatient psychiatric services are provided typically for PwIDs (Casanova Dias et al, 2020; Krysta et al, 2019). However, the current reform underway in the pediatric mental health system, together with changes in the mode of training specialists, should improve the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of mental disorders among Polish PwID is up to three times higher than in the general population, they lack adequate diagnostic tools and specialists (Rękosiewicz, 2018). No special category for ID Psychiatry exists in Polish psychiatric training, and no inpatient or outpatient psychiatric services are provided typically for PwIDs (Casanova Dias et al, 2020; Krysta et al, 2019). However, the current reform underway in the pediatric mental health system, together with changes in the mode of training specialists, should improve the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…More published research and improvements in clinical training to serve individuals who are MV and others with severe developmental disabilities are urgently needed. The present undertraining of psychiatrists for this challenging task requires attention globally, including in the USA [27].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, literature from other countries demonstrates that insufficient training of psychiatrists in the care of patients with ASD/ID is a global concern, particularly given a pervasive shortage of psychiatrists, with many low-income and middle-income countries having one psychiatrist for every 200,000 people (World Health Organization [WHO], 2013). Recent reviews of training standards in ID for psychiatrists in the European Union (Dias et al, 2020) and overall psychiatry training in Asia (Isaac et al, 2018) have identified multiple training deficits, including wide variance in the rigor and availability of training, with no required ID training in some countries, a lack of unified minimum training standards, a mismatch between the prevalence of a condition and the amount of training, and limited trainee supervision. These disparities were noted to compromise the quality of psychiatric care by contributing to inconsistent and fragmentary treatment across the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…These findings mirror reports from psychiatrists in other countries, including Canada (Lunsky et al, 2007), the United Kingdom (Kaushal et al, 2018), Australia (Edwards et al, 2007), Singapore (Sajith et al, 2019), and Israel (Werner et al, 2013). Experts in the field, both in the United States and internationally, have repeatedly recommended expanding training in this area (Bouras, 1992; Dias et al, 2020; Menolascino & Fletcher, 1992; Ruedrich et al, 2007; Syzmanski et al, 1991; Torr et al, 2008). In a 2009 study assessing psychiatry training in both ASD and ID in the United States, CAP and GEN directors of programs accredited by the Accreditation Council for Graduate Medical Education (ACGME) were surveyed about lecture hours and patient experiences in ASD/ID in their respective programs (Marrus et al, 2014).…”
mentioning
confidence: 99%